Efektivitas Ketebalan Media Filter Arang Aktif Bambu dengan HCI untuk Menurunkan Warna dengan Filtrasi Upflow - Ataria Ariandani (Fakultas Teknik, 2025)
Water color pollution by domestic and industrial waste is one of the environmental issues that needs to be handled effectively to maintain the quality of the water environment. This study aims to determine the effectiveness of bamboo charcoal filter media thickness activated using 15% HCl solution with an upflow filtration system on the removal of 312,71 and 355,42 Pt-Co color levels. Activated bamboo charcoal was chosen as the media because of its abundant availability and has good pore properties after the chemical activation process. Variations in filter media thickness used were 5 cm, 10 cm, and 15 cm, with a constant flow rate. Color levels before and after the filtration process were analyzed using a Uv-Vis spectrophotometer. The results showed that the increase in media thickness was directly proportional to the color removal efficiency. The media thickness of 15 cm gave the highest removal efficiency of 71%, indicating that the thicker the charcoal media, the greater the adsorption capacity of color-causing compounds. The upflow filtration system also supports the adsorption process by maximizing the contact time between water and media.The data were analyzed using Analysis of Variance. Prior to the Analysis of Variance test, assumptions of normality and homogeneity of variances were verified. The normality test yielded a p-value of 0.3966, and the homogeneity test (Levene’s test) resulted in a p-value of 0.6853, indicating that both assumptions were satisfied (p > 0.05). The statistical analysis using the Two-Way ANOVA test yielded p-values of 5.54 × 10⁻¹⁴ for the variation in filter media thickness and 1.19 × 10⁻⁶ for the variation in initial wastewater color concentration. These low p-values indicate a significant effect on the reduction of color concentration (p-value < 0.05).
Entry oleh Arif 2026 April 01
Keywords: Activated bamboo charcoal; ANOVA; Color removal efficiency; Pt-Co (Platinum Cobalt); Upflow filtration